An In-vitro Model to Study Device-induced Thrombosis and Embolism: - Sukavaneshvar, Sivaprasad; Solen, Kenneth A.; Mohammad, Syed F. (Thrombosis and Haemostasis, 2000)
A bovine in-vitro model was developed to investigate device-induced thromboembolism (TE) and its pharmacological intervention, using a stent as a prototype device. Emboli were assessed continuously using a light-scattering microemboli detector (LSMD). Thrombus on the stent was assessed gravimetrically at the end of the experiment. The contribution of the stent as the predominant source of detectable thromboemboli in this model was verified by placing LSMD probes upstream and downstream of the stent. The effectiveness of ethylenedinitrilo-tetraacetic-acid (EDTA) and three anti-thrombogenic agents (aspirin, dipyridamole, and tirofiban) for mitigating device-induced TE was also assessed. The results show that 1) the model has potential to study device-induced TE and the efficacy of possible interventional strategies, 2) the LSMD is capable of continuous, non-invasive, real-time assessment of embolism, 3) the assessment of embolization may constitute an important part of evaluating hemocompatibility, 4) tirofiban is effective in reducing both stent-induced thrombosis and embolism above certain concentrations.
Keywords: Thrombosis; thromboembolism; stent; tirofiban; aspirin; dipyridamole